Glutathione S–Transferase Polymorphisms (GSTM1, GSTT1, GSTP1) and Male Factor Infertility Risk: A Pooled Analysis of Studies - Mohammad Reza Safarinejad (Urology Journal, 2012)
PURPOSE: To determine the role of glutathione S-transferases (GSTs; GSTM1, GSTT1, and GSTP1) gene polymorphisms in susceptibility to male factor infertility. MATERIALS AND METHODS: We report a pooled analysis of 11 studies on the association of GSTM1, GSTT1, and GSTP1 polymorphisms and male factor infertility, including 1323 cases and 1054 controls. RESULTS: An overall significant association was determined between the GSTM1 null genotype [odds ratio (OR), 2.74; 95% confidence interval (CI), 1.72 to 3.84; P = .003], GSTT1 null genotype (OR, 1.54; 95% CI, 1.43 to 3.47; P = .02), and male factor infertility. The GSTP1 Ile/Val genotype had overall protective effect against development of infertility (OR, 0.48; 95% CI, 0.27 to 0.77), while there was significant heterogeneity between studies. In sensitivity analysis, two studies were excluded; the association and direction between GSTM1 and GSTT1 null genotypes and GSTP1 Ile/Val genotype and male infertility remained unchanged. There was no significant interaction between smoking status and studied genotypes on male infertility risk (P = .26). CONCLUSION: These results demonstrated that amongst populations studied to date, GSTM1 and GSTT1 null genotypes are associated with strong and modest increase in the risk of male infertility, respectively. On the contrary, GSTP1 Ile/Val genotype has protective effect.